(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the influence of anatomical characteristics on the adhesion performance of Vatairea sp., Paulownia sp., Aspidosperma populifolium and Tectona grandis wood. Specimens for anatomical, physical and mechanical analyzes were produced from tangentially oriented boards. The treatments were joint glued from pieces of the same anatomical orientation (radial and tangential), evaluated for shear strength and glue line failure. The Vatairea sp wood had the highest specific gravity (0.74 g cm-3) and the Paulownia sp (0.34 g cm-3) wood was smaller. Aspidosperma populifolium species showed the highest shear strength in the glue line in the tangential and radial faces. The anatomical variables with higher influence on the wood adhesion process were pith ray cells and especially fibers that exhibit the greatest correlation with the shear strength of the glue line.